Pengembangan Aplikasi Android Sistem Informasi Perpustakaan Sekolah - Faiz Wahyu Perdana Rangkuti; Muhammad Alda (Teknik: Jurnal Ilmu Teknik dan Informatika, 2025)
This research stems from the problem of manual book lending management in libraries, which often leads to obstacles such as delays in recording, data errors, and difficulties in monitoring collections. The main objective of this research is to design and develop a web-based library information system that can facilitate member data management, borrowing, and returning, as well as providing real-time book availability information. The method used is software development with a structured approach, through the stages of needs analysis, design, implementation, and testing with black box testing. The results of the study indicate that the system built is able to meet user needs, as evidenced by the successful testing that carried out all main functions without errors. The implications of this research are increased efficiency in library management and ease for students in borrowing and checking book availability. However, this research still has limitations in advanced features such as integration with the attendance system or automatic fine payments, so that these can be developed in future research.